2014
DOI: 10.1177/0883073814527161
|View full text |Cite
|
Sign up to set email alerts
|

Reference Range of Fetal Transverse Cerebellar Diameter Between 18 and 24 Weeks of Pregnancy in a Brazilian Population

Abstract: To determine a reference range of fetal transverse cerebellar diameter in Brazilian population. This was a retrospective cross-sectional study with 3772 normal singleton pregnancies between 18 and 24 weeks of pregnancy. The transverse cerebellar diameter was measured on the axial plane of the fetal head at the level of the lateral ventricles, including the thalamus, cavum septum pellucidum, and third ventricle. To assess the correlation between transverse cerebellar diameter and gestational age, polynomial equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…Excluded studies and reasons for exclusion are reported in Table S3 . Finally, 42 studies, reported between January 1970 and 2021, met the inclusion criteria, and these provided data for 45,626 fetuses, included in the final analysis ( Table 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The median sample size of participating fetuses was 372.5 (range: 50 to 8313; 25th percentile: 175.8; 75th percentile: 709.3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluded studies and reasons for exclusion are reported in Table S3 . Finally, 42 studies, reported between January 1970 and 2021, met the inclusion criteria, and these provided data for 45,626 fetuses, included in the final analysis ( Table 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The median sample size of participating fetuses was 372.5 (range: 50 to 8313; 25th percentile: 175.8; 75th percentile: 709.3).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported more than one fetal brain structure [ 9 , 10 , 17 , 32 , 34 , 36 , 41 , 42 , 43 ]. In addition, 4 studies reported charts for POF [ 9 , 10 , 17 , 36 ], 6 for SF [ 9 , 10 , 17 , 35 , 36 , 44 ], 3 for AV [ 22 , 36 , 43 ], 14 for PV [ 7 , 8 , 14 , 19 , 23 , 26 , 27 , 30 , 32 , 34 , 36 , 38 , 40 , 43 ], 20 for TCD [ 12 , 15 , 16 , 18 , 20 , 21 , 24 , 25 , 28 , 31 , 32 , 34 , 39 , 41 , 42 , 43 , 45 ,…”
Section: Resultsmentioning
confidence: 99%
“…Using different planes for fetal head biometry can lead to significant measurement differences 33 . In some studies, landmarks for plane acquisition were not specified 34–44 , while in others, various oblique planes with numerous landmarks were proposed 45,46 . One of the strengths of our study is the use of standardized axial planes recommended in routine clinical practice for biometry assessment (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Using the ultrasonographic technique or MRI investigation, recent studies determine different parameters of cerebellar development to establish the developmental age. Ultrasound studies highlight the importance of the transverse cerebellar diameter (TCD) or vermis dimensions as an alternative procedure to the appreciation of gestational age by the measurement of biparietal diameter (BPD) of the skull [ 9 12 ]. Another tool of imaging determination, the MRI technique, gives the possibility to study the volume of developmental cerebellum as a more accurate parameter in relation with gestational age.…”
Section: Background and Aimsmentioning
confidence: 99%